2022
DOI: 10.1007/s40487-022-00210-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electronic Patient-Reported Outcome Measures in Assessing Smoking Status and Cessation for Patients with Lung Cancer

Abstract: Introduction: Smoking cessation following lung cancer diagnosis is recommended to improve patient outcomes. Electronic Patient Reported Outcome Measures (ePROMs) may be useful for identifying and facilitating cessation support in patients that continue to smoke after a cancer diagnosis. The primary aim was to investigate the level of agreement between clinician-reported and self-reported patient smoking status during the first visit to a cancer centre (I). Secondary aims included investigating differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…According to our findings, we found several significant advantages of ePRO systems in cancer care: “Improved Quality of Life and Care,” “Real-time and Remote Monitoring,” and “Effective Communication Between Clinicians and Patients.” The most prominent advantage identified was the “Improved Quality of Life and Care”. 14 16 , 18 , 31 71 This finding is consistent with the study by Gressel et al, which emphasized the prevalence of web-based ePRO systems for long-term monitoring and patient empowerment. 101 Similarly, Moradian et al’s exploration of an eHealth tool for capturing and analyzing immune-related adverse events in cancer treatment 31 and Helissey et al’s assessment of the effectiveness of electronic patient reporting outcomes in prostate cancer care further contributed to understanding the benefits of ePRO systems in cancer care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our findings, we found several significant advantages of ePRO systems in cancer care: “Improved Quality of Life and Care,” “Real-time and Remote Monitoring,” and “Effective Communication Between Clinicians and Patients.” The most prominent advantage identified was the “Improved Quality of Life and Care”. 14 16 , 18 , 31 71 This finding is consistent with the study by Gressel et al, which emphasized the prevalence of web-based ePRO systems for long-term monitoring and patient empowerment. 101 Similarly, Moradian et al’s exploration of an eHealth tool for capturing and analyzing immune-related adverse events in cancer treatment 31 and Helissey et al’s assessment of the effectiveness of electronic patient reporting outcomes in prostate cancer care further contributed to understanding the benefits of ePRO systems in cancer care.…”
Section: Discussionsupporting
confidence: 92%
“…According to Table 1 , The advantages of ePRO were found to be diverse, with “Improved Quality of Life and Care” being the most prominent, cited in 45 studies (28.48%). 14 16 , 18 , 31 71 This was followed by “Real-time and Remote Monitoring” with 39 references (24.68%), highlighting its significance in real-time health monitoring, which can significantly impact patient outcomes 1 , 16 18 , 31 , 33 , 34 , 36 39 , 43 , 44 , 47 , 49 …”
Section: Resultsmentioning
confidence: 99%
“…(5/12) from the United Kingdom, 17% (2/12) from the Netherlands, and 8% (1/12) from each of the following country: Germany, Canada, Australia, the United States, and Italy. All Crockett et al [24] Qualitative studies United Kingdom 2021 Patient and clinician opinions of patient reported outcome measures (PROMs) in the management of patients with rare diseases: a qualitative study Aiyegbusi et al [25] Systematic reviews Germany 2020 Implementation of patient-reported outcome assessment in routine cancer care: A systematic review of multicentric programs in Europe Scheibe et al [26] Factors for implementation Canada 2021 A multi-level approach for the use of routinely collected patientreported outcome measures (PROMs) data in healthcare systems Al Sayah et al [27] Factors for implementation United Kingdom 2020 An emerging framework for fully incorporating PI a into PROMs Carlton et al [28] Factors for implementation United States 2018 Implementing electronic patient reported outcomes measurements: challenges and success factors Nordan et al [29] Qualitative studies Australia 2022 Stepping into the real world: a mixed-methods evaluation of the implementation of electronic patient reported outcomes in routine lung cancer care Girgis et al [30] Presentation of experiences United Kingdom 2022 The Role of Electronic Patient-Reported Outcome Measures in Assessing Smoking Status and Cessation for Patients with Lung Cancer Convill et al [31] Systematic reviews United Kingdom 2022 Prognostic value of patient-reported outcome measures (PROMs) in adults with non-small cell Lung Cancer: a scoping review Liao et al [32] Systematic reviews The Netherlands 2017 Patient-reported outcome measures (PROMs) in the management of lung cancer: A systematic review Bouazza et al [33] Qualitative studies Italy 2022 Knowledge, use and attitudes of health care professionals towards patient-reported outcome measures (PROMs) at a comprehensive cancer center Brunelli et al [34] Systematic reviews The Netherlands 2020 Benefits and Disadvantages of Electronic Patient-reported Outcome Measures: Systematic Review Meirte et al [35] a PI: public involvement.…”
Section: Extraction and Graphical Representation Of Resultsmentioning
confidence: 99%
“…Crockett et al [24], 2021 An independent questionnaire, such as the ePROM, would be well suited to help identify patients who still smoke. Convill et al [31], 2022…”
Section: Brunelli Et Al [34] 2022mentioning
confidence: 99%
See 1 more Smart Citation